Seroprevalence of hepatitis E virus in HIV-infected patients in China. (10th September 2017) - Zeng, Hang; Wang, Lin; Liu, Peng; Liao, Lingjie; Wang, Ling; Shao, Yiming
Abstract : N/A: The seroprevalence of hepatitis E virus (HEV) in HIV-infected patients in China has never been reported. Thus, anti-HEV in HIV-infected patients recruited in five provinces in China was tested. The seroprevalence of HEV was 39.7%, which was higher than that in the general population (23.5%). HEV infection might be a frequent cause of hepatitis in HIV-infected patients. Abstract : Supplemental Digital Content is available in the text